Strengths, weaknesses, opportunities and threats of football industry in the Iranian Mazandaran Province - Darzi Khelradi, R.; Hami, M.; Shojaei, V.; Sanai, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The objective of this study was to analyze the strengths, weaknesses, opportunities and threats of football industry in the Iranian Mazandaran Province. The sample of the present study consisted of 80 football experts (92.5% males and 7.5% females). The instrument used was a valid and reliable questionnaire consisting of four parts: 1- Strengths (17 questions), 2- Weaknesses (25 questions), 3- Opportunities (13 questions) and 4- Threats (19 questions). The statistical analysis was carried out with SPSS 24. The results showed that Mazandaran football industry had more weaknesses than strengths and more threats than opportunities. Considering these results, the authors propose a series of strategies to improve the football industry of this province using the SWOT approach.